Pengaruh Sertifikasi Halal, Produk dan Religius Terhadap Persepsi Mahasiswa Ekonomi Syariah IAIN Pontianak Pada Produk Pro Israel - Kantari, Samawa; Deti, Sri; Ubabuddin (STKIP MAJENANG, 2025)
This study aims to identify: 1) The effect of halal certification on the perceptions of students of the Islamic Economics program at IAIN Pontianak regarding Pro-Israel products. 2) The effect of the product on the perceptions of students of the Islamic Economics program at IAIN Pontianak regarding Pro-Israel products. 3) The effect of religiosity on the perceptions of students of the Islamic Economics program at IAIN Pontianak regarding Pro-Israel products. The method used in this research employs a quantitative method. Data collection was conducted through the distribution of questionnaires to respondents. The data analysis used is panel data, and the hypothesis testing uses the coefficient of determination (R2), partial (t-test). The data used by the researcher is primary data that is then processed into secondary data, which includes halal certification, products, religiosity, and student perceptions. Data testing was also conducted with the help of SPSS 25 and Eviews 12 applications. The results of this study show: 1) The halal certification variable has a significant partial effect on student perceptions, as indicated by a t-statistic value of 1.6157 and a probability (p) of 0.0190. 2) The product variable has a significant partial effect on student perceptions, as indicated by a t-statistic value of 0.481082 and a probability value of 0.0314 < 0.05. 3) The religious variable has a significant partial effect on student perceptions, as indicated by a t-statistic value of 6.9607 and a probability of 0.000 < 0.05.